2021
DOI: 10.1371/journal.pgph.0000040
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of specificity and sensitivity of a standard SARS-CoV-2 antigen rapid diagnostic test: A prospective study at a teaching hospital in Northern Ghana

Abstract: The testing capacity for SARS-CoV-2 in Africa is rather limited. Antigen detection rapid diagnostic tests (Ag-RDTs) are a cheap and rapid alternative to reverse transcriptase-polymerase chain reaction (RT-PCR) tests, but there is little data about their performance under real life conditions in tropical countries. The objective of this study is to evaluate the performance of a standard Ag-RDT in a population of a major hospital in northern Ghana. Prospective, cross-sectional, blinded verification of the perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…Although the STANDARD Q maintained a high specificity of 99% in the field, the test had a reduced sensitivity of 56%. Supporting our findings, field studies in African cohorts on the STANDARD Q conducted in Cameroon and Ghana reported an overall sensitivity of 59% and 64% respectively [ 21 , 22 ]. The high sensitivity observed in the laboratory might have been due the biased sampling of choosing an equal number of positive and negative samples compared to the randomness in the field of getting a much smaller proportion of individuals testing positive for COVID-19.…”
Section: Discussionsupporting
confidence: 87%
“…Although the STANDARD Q maintained a high specificity of 99% in the field, the test had a reduced sensitivity of 56%. Supporting our findings, field studies in African cohorts on the STANDARD Q conducted in Cameroon and Ghana reported an overall sensitivity of 59% and 64% respectively [ 21 , 22 ]. The high sensitivity observed in the laboratory might have been due the biased sampling of choosing an equal number of positive and negative samples compared to the randomness in the field of getting a much smaller proportion of individuals testing positive for COVID-19.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the low performance in the group with <7 days of symptoms suggests underreporting or possibly different perceptions of the duration of symptoms in different cultures. Also, the impact of environmental conditions (i.e., high temperature and high humidity) could be considered ( 8 , 9 ). Of note, FIND repeatedly observed lower test sensitivity in the evaluations performed at the study site in India.…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates, 11,462 articles were screened and 433 papers were considered eligible for full-text review. Of these, 259 were excluded because they did not present primary data or the Ag-RDT was not commercially available, leaving 174 studies to be included in the systematic review [16-189]. A list of the studies excluded and their reason for exclusion can be found in the Supplement (S4 Text).…”
Section: Resultsmentioning
confidence: 99%
“…At the end of the data extraction process, 21 studies were still in preprint form [16, 17, 21, 47, 50, 55, 58, 65, 69, 74, 84, 100, 116, 121, 129, 160, 167, 168, 173, 174, 186]. All studies were written in English, except for 3 in Spanish [53, 62, 134], 1 in Turkish [95], and 1 in French [153].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation